Engineered biomimetic micro/nano-materials for tissue regeneration - Han, Feng; Meng, Qingchen; Xie, En; Li, Kexin; Hu, Jie; Chen, Qianglong; Li, Jiaying; Han, Fengxuan (Frontiers in Bioengineering and Biotechnology, 2023)
The incidence of tissue and organ damage caused by various diseases is increasing worldwide. Tissue engineering is a promising strategy of tackling this problem because of its potential to regenerate or replace damaged tissues and organs. The biochemical and biophysical cues of biomaterials can stimulate and induce biological activities such as cell adhesion, proliferation and differentiation, and ultimately achieve tissue repair and regeneration. Micro/nano materials are a special type of biomaterial that can mimic the microstructure of tissues on a microscopic scale due to its precise construction, further providing scaffolds with specific three-dimensional structures to guide the activities of cells. The study and application of biomimetic micro/nano-materials have greatly promoted the development of tissue engineering. This review aims to provide an overview of the different types of micro/nanomaterials, their preparation methods and their application in tissue regeneration.